From Manchester to Alexandria: Are there fundamentals of communication teaching: Presenter(s): Emmanuel Oladipo, Universtity of Manchester, United Kingdom. (April 2023) - Allam, Sonia; Corfield, Douglas; Shepherd, Sarah
Abstract : Background: The University of Manchester has a collaboration agreement for the joint delivery and award of MBChB/MBBCH with the University of Alexandria, Egypt. Medical students studying in Alexandria will therefore undertake the Manchester clinical communication course. This course is established on relationship-based teaching, frequent experiential sessions, and patient centred care. Reflecting specifically on the translation of the clinical communication course this presentation will discuss the challenges and opportunities in translating a UK based curriculum to Egypt. Methods: The University of Alexandria have begun delivery of the Manchester curriculum. We will reflect on our experience of training staff in Alexandria, queries that were raised and how we responded to them and feedback about how delivery of the communication curriculum is progressing so far, with demonstration of adapted materials. Findings: Some of the challenges posed include: how to respond to different cultural norms both in the approach to teaching and in the patient scenarios used in the sessions and identifying where session content can be adapted to suit the context yet does not change significantly the core learning outcomes of the sessions. An unanticipated and significant challenge raised was the use of British colloquial language in session notes not understood by our Egyptian colleagues. Discussion: This collaboration poses several questions: − Are there fundamental aspects of communication that should exist across cultures? − What aspects of communication teaching require cultural and contextual adaptation? How ought this to be managed where a joint degree will be awarded? − UK doctors are delivering healthcare to an increasingly diverse patient population, are we equipping students to navigate the different health care needs and expectations of patients with different cultural backgrounds? − International students come to programme with a different set of expectations around health care provision and approaches – are we supporting them fully?